49.7k views
0 votes
Evaluate each using the values given. P-q ÷ 3; use p= 4, and q = 3​

2 Answers

3 votes

Answer:

3

Explanation:

p - q ÷ 3 = ?

First, substitute in 3 for q and 4 for p

4 - 3 ÷ 3 = ?

You divide first because of the PEMDAS rule (Parenthesis, Exponents, Multiplication Division (left to right) Addition Subtraction (left to right)

4 - 1 = ?

Subtract to get your answer:

3

I hope this helps :)

User Jakob
by
4.9k points
1 vote
0.33 because you have 4-3=1 so 1 ÷ 3=0.33
User Gauteh
by
4.7k points